2015
DOI: 10.1590/so100-720320150005279
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da lesão HPV induzida em canal anal de mulheres com neoplasia intraepitelial cervical 2 e 3: um estudo de corte transversal

Abstract: Women with CIN grade 2/3 showed a high prevalence of anal HPV infection and HPV-induced lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
4
0
2
Order By: Relevance
“…Most studies about anal intraepithelial neoplasia are performed in HIV-positive patients and in men who have sex with men. Studies in patients with immunocompetent CIN II and CIN III, as those in this study, are scarce [11].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most studies about anal intraepithelial neoplasia are performed in HIV-positive patients and in men who have sex with men. Studies in patients with immunocompetent CIN II and CIN III, as those in this study, are scarce [11].…”
Section: Discussionmentioning
confidence: 92%
“…Data similar to the ones in the literature were found in this research, as a considerable higher number of patients who consume alcohol beverages was observed in the study group. Heráclio, et al [11] cited more than 50% of patients with CIN II and CIN III being alcohol consumers [18].…”
Section: Discussionmentioning
confidence: 99%
“…Com esses mesmos percentuais de sensibilidade e especificidade na citologia pelo teste de Papanicolau, corrobora Leeds & Fang (2016), na sua revisão sistemática. No estudo transversal de Heráclio (2015), a citologia anal apresentou alta sensibilidade (98%) e baixa especificidade (50%), todavia, no estudo de Leal et al (2020), ficou evidenciado que a citologia anal, globalmente, está descrita em 69% a 93% para a sensibilidade e de 32% a 59% para especificidade.…”
Section: Resultsunclassified
“…No recém-nascido a transmissão do HPV pode acontecer pelas vias de parto e no processo de amamentação (GARCEZ et al, 2016). A principal via de transmissão do HPV é a sexual que inclui: contato oral-genital, genital-genital ou mesmo anal-genital (BARROS; MOREIRA; MENEZES, 2021), e pelos dedos ou no contato de objetos com o canal anal (HERÁCLIO, 2015).…”
Section: Introductionunclassified
“…The authors explain this excellent performance by the fact that the samples were collected by medical and nursing students specially trained in the procedure. Another study by Heráclio et al 25 reported that 7% of the conventional samples were unsatisfactory. Meanwhile, Albuquerque et al 9 recommend that the proportion of unsatisfactory samples in this group should be less than 5%, while we obtained 11.25%, showing that there is room for improvement in the sample collection procedures in our institution.…”
Section: Discussionmentioning
confidence: 97%